139. association of Physician Orders for Life-sustaining Treatment (POLST) with Antimicrobial Use at End of Life in Cancer Patients: An Antimicrobial Stewardship Opportunity. (31st December 2020) - Kates, Olivia; Krantz, Elizabeth M; Lee, Juhye; Klaassen, John; Morris, Jessica; Mezheritsky, Irina; Sweet, Ania; Tverdek, Frank; Loggers, Elizabeth T; Pergam, Steven A; Liu, Catherine
Abstract: Background: IDSA/SHEA guidelines recommend that antimicrobial stewardship programs support providers in antibiotic decisions for end of life care. Washington State Physician Orders for Life-Sustaining Treatment (POLST) forms allow patients to indicate antimicrobial use preferences. We sought to characterize antimicrobial use in the last 30 days of life for cancer patients by presence of a POLST and antimicrobial use preferences. Methods: We performed a single-center, retrospective cohort study of cancer patient deaths from January 1, 2016 - June 30, 3018. Patient demographics, clinical characteristics, POLST, and antimicrobial use within 30 days before death were extracted from electronic records. To test for an association between POLST completed at least 30 days before death and inpatient antimicrobial days of therapy (DOT) in the 30 days before death, we used negative binomial models adjusted for age, sex, race, and service line (hematologic versus solid malignancy); model estimates are presented as incidence rate ratios (IRR) with 95% confidence intervals (CI) Results: Of 1796 patients, 406 (23%) had a POLST. 177/406 (44%) were completed less than 30 days before death, and 58/177 (32.8%) specified limited antibiotic use; 40/177 (23%) did not specify any antimicrobial use preference (Fig 1). Of 1295 patients with at least 1 inpatient day in the 30 days before death, 1070 (83%) received at least 1 inpatient antimicrobial with median DOT of 1077 per 1000 inpatient days (Tab 1). There was no difference in DOT among patients with and without a POLST > /= 30 days before death (IRR 0.92, CI 0.77, 1.10). Patients with a POLST specifying limited antibiotic use had significantly lower inpatient IV antimicrobial DOT compared to those without a POLST (IRR 0.64, CI 0.42–0.97) (Fig 2). Figure 1. Classification of Patients by Presence of POLST, Timing, and Antimicrobial Preference Content of POLST. Numbers shown represent the number of patients (percentage). Full antibiotic use refers to the selection "Use antibiotics for prolongation of life." Limited antibiotic use refers to the selection "Do not use antibiotics except when needed for symptom management." Table 1: Antimicrobial use for all patients and by advance directive group Figure 2. Forest plot of model estimates, represented as incidence rate ratios (IRR) with 95% confidence intervals (CI), for associations between POLST antimicrobial specifications completed at least 30 days before death and inpatient antibiotic days of therapy (DOT) in the 30 days before death. Estimates represent comparisons between each POLST category and no POLST completed at least 30 days before death. Dots represent the IRR and brackets extend to the lower and upper limit of the 95% CI. Blue estimates are for the inpatient antibiotic DOT outcome and red estimates are for the inpatient IV antibiotic DOT outcome. Conclusion: POLST completion is rare > /= 30 days before death, with few POLSTs specifying antimicrobial use. Compared to those with no POLST in this time frame, patients who indicated that antibiotics should be used only for symptom management received significantly fewer inpatient IV antimicrobials. Early discussion of advance directives including POLST with specification of antimicrobial use preferences may promote more thoughtful use of antimicrobials near the end of life in a compassionate, patient-centered way. Disclosures: Steven A. Pergam, MD, MPH, Chimerix, Inc (Scientific Research Study Investigator)Global Life Technologies, Inc. (Research Grant or Support)Merck & Co. (Scientific Research Study Investigator)Sanofi-Aventis (Other Financial or Material Support, Participate in clinical trial sponsored by NIAID (U01-AI132004); vaccines for this trial are provided by Sanofi-Aventis)